THE GROWTH OF JACKFRUIT (ARTOCARPUS HETEROPHYLLUS L.) SHOOTS ON VARIOUS CONCENTRATION BENZYLAMINO PURINE (BAP) IN VITRO - Frisca Nanda Bulo; Enny Adelina; Ramal Yusuf; Hawalina Kasim (Tadulako University, 2018)
The development of Central Sulawesi superior commodity,which is Tulo-5, the drough-resistant cultivars, through tissue culture technique can be used as an alternative, in addition to conventional breeding. This study aims to determine the growth of jackfruit shoots in various concentrations of benzylamino purine in vitro. The research has been conducted at the Laboratory of Plant Biotechnology, Agriculture Faculty of Tadulako University, Palu. The research began on December 2017 and ended up on February 2018. This research used Completely Randomised Design of one-factor treatment which is BAP concentrations consist of 4 stage which is1,5 ppm BAP, 2,0 ppm BAP, 2,5 ppm BAP, 3,0 ppm BAP. The result showed that 6 weeks after planting, BAP concentration had significant effect on shoots time to emerge and shoots number but no significant effect on leaf number. The result of Tukey’s HSD test showed that concentration2,5 ppm gave the fastest shoot emergence with an average of 2,875 days after planting, in concentration 2,0 ppm gave the highest number of shoots with an average of 2.125 shoots per explant, and for the highest number of leaves found in the concentration of 2,0 ppm with the average number of leaves is 1 strand per explant.